Internalisasi Nilai Sipakatau, Sipakalebbi, dan Sipakainge Dalam Pembentukan Perilaku Etis Akuntan Syariah - Sri Ramadhani; St Nurhayati; Fibryani Qalsyum; Intan Azis; Hasna Inna; Yusriani Yusriani (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The rapid growth of the Islamic financial industry in Indonesia requires sharia accountants to possess not only technical competence but also strong ethical integrity. This study aims to examine the internalization of Bugis-Makassar cultural values, namely Sipakatau, Sipakalebbi, and Sipakainge’, in shaping the ethical behavior of sharia accountants. The research employs a descriptive qualitative approach through library research by analyzing Lontara manuscripts, particularly Latoa, as well as anthropological literature, Islamic accounting ethics, and contemporary professional ethics studies. The findings reveal that Sipakatau (humanizing others) encourages accountants to uphold honesty, transparency, and accountability in financial reporting. Sipakalebbi (mutual respect) strengthens professionalism, respect for ethical standards, and responsible behavior in carrying out professional duties. Meanwhile, Sipakainge’ (mutual reminding) functions as a moral control mechanism that supports whistleblowing practices, fraud prevention, and ethical organizational culture. These cultural values operate as a form of soft control that complements formal ethical standards established by professional accounting institutions and Islamic financial regulations. Furthermore, the integration of local wisdom with Islamic ethical principles contributes to the development of accountants who are trustworthy, professional, and socially responsible. Therefore, the study concludes that the incorporation of Bugis-Makassar cultural values into sharia accounting ethics is strategically important for strengthening accountability, professionalism, and public trust in Islamic financial institutions in Indonesia.